Mechanistic Studies of Non-Enzymatic (Per)Oxidation Pathways of Thiols, Sulfenic Acids and Lipids under Biomimetic Conditions - Saraev, Dmitry (Université d'Ottawa / University of Ottawa, 2025)
To facilitate the metabolic processes needed to sustain life, aerobic lifeforms have evolved to utilize atmospheric oxygen (O₂) as the terminal electron acceptor to generate essential energy. While aerobic metabolism is highly efficient compared to its anaerobic counterpart, one of its drawbacks is the potential for the formation of so-called "reactive oxygen species", which engage in a series of chemical processes that lead to the formation of non-enzymatic metabolites, of which some are harmful to cellular proliferation and may act as molecular signatures for pathology. Among these "reactive oxygen species" are organic (hydro)peroxides (ROOHs) derived from lipids and other biomolecules. Thiols, in the form of the amino acid cysteine and its derivative, glutathione, are key reductants that eucaryotic cells have evolved to utilize to prevent the accumulation of ROOHs, among many other functions. Despite being central to many aspects of biology, the mechanisms of thiol reactivity have been challenging to characterize, as electrophilic reaction intermediates, like sulfenic acids (RSOH) and sulfenyl chlorides (RSCl), are too reactive to be observed directly. To be able to observe these intermediates in aqueous buffer and to develop a better understanding of the mechanistic underpinnings of thiol oxidation, a fluorinated triptycene thiol was synthesized and its reactivity with H₂O₂, ¹O₂ and HOCl was investigated. Ferroptosis, an iron-dependent form of cellular death, is strongly associated with the accumulation of lipid hydroperoxides (LOOHs) and the chemical processes that occur as a result. Numerous studies support an intricate relationship between a cell's lipidome and its sensitivity to ferroptosis, however, the molecular basis for this relationship remains poorly understood. To determine whether the ability to initiate and promote iron-dependent LPO is dependent on the structure and reactivity of a ROOH, different ROOHs were individually incorporated into eggPC liposomes and their ability to initiate LPO through addition of Fe(II) was investigated using STY-BODIPY as a fluorescent reporter of autoxidation (the spontaneous reaction of a compound with atmospheric oxygen). Results obtained upon screening various iron chelators in place of EDTA strongly support iron-phospholipid association, ligand displacement on Fe(II) by hydroperoxyl and subsequent inner-sphere reductive heterolysis of LOOHs as the primary chemical steps in LPO initiation. The rate of STY-BODIPY oxidation (and hence, LPO) depends on the position of the hydroperoxyl group (-OOH), where the rate increases as the -OOH is further down the alkyl chains of fatty acids. The obtained results corroborate a theory where physical (H-bonding between membrane components and orientation of the peroxyl group of LOOHs and chemical (association of low molecular weight iron species with the membrane and their ability to reduce LOOHs at the interface, competing LOOH decomposition pathways) effects dictate a lipid bilayer's susceptibility to peroxidation.
Keywords: oxidation; ferroptosis; lipid peroxidation; sulfenic acid